Sonographic evaluation of Intima-Media thickness of carotid artery in healthy, hypertensive and diabetic Nepalese population - Regmi, Shubhekshya; sharma, Saroj; Khadka, Hensan (Journal of Gandaki Medical College-Nepal, 2020)
Introduction: Hypertension and Diabetes are two major risk factors for atherosclerotic disease. Carotid artery intima media thickness(cIMT) is considered a reliable surrogate measure for diagnosing subclinical atherosclerosis, its progression and regression. Paucity of available data regarding mean value of cIMT highlights the importance of defining the cut off value of cIMT in a specified population. Very limited studies have been done on sonographic evaluation of mean cIMT and carotid artery injury in hypertension and diabetes in Nepalese population. This study, therefore aims to determine mean cIMT in Nepalese population and to analyze effect of Hypertension and diabetes on cIMT. Methods: Cross-sectional hospital based study was conducted within the period of 18 months. B-mode ultrasound was used to measure cIMT in bilateral common carotid arteries. Comparison of mean cIMT was done amongst healthy, hypertensive and diabetes with hypertensive patients. Duration of disease was also considered. Data analysis was done with “R” analytical study. Results were expressed as mean ± standard deviation. Results: Total1005 (508 female and 497 male) adult patients with age range of 30 to 85 years were assessed. Among these 329(32.74%) were healthy adults, 341(33.93%) were hypertensive and 335(33.33%) were diabetes with hypertensive patients. The mean cIMT in cases was more than controls (P < 0.001) bilaterally with diabetes having an additive effect. There was also positive correlation of measured value with duration of disease and age of patients. Conclusion: The present study found that mean cIMT in cases was more than controls. There is an additional effect of Diabetes on cIMT in hypertensive patient. Age and duration of disease can accelerate atherosclerosis.